Technology system integration of hardware and software data protection - Alishоv, N.I.; Marchenko, V.A.; Mishchenko, A.N. (PROBLEMS IN PROGRAMMING, 2025)
The article deals with the creation of hardware and software data protection. The analysis of characteristics of a hardware device based on digital signal processors for implementation of perfectly secure encryption. The algorithms of matching the required parameters between two remote devices. Describes software and hardware protection systems streaming.Prombles in programming 2011; 3: 58-68